Evaluation of the macro elemental composition of the equine third metacarpal bone - Selim, Mariana Baroni; Mota, Taís; Aburaya, Jim Heiji; Vechiato, Thales Anjos de Faria; De Zoppa, André Luis do Valle (Brazilian Journal of Veterinary Research and Animal Science, 2012)
The equine third metacarpal bone has been seen as a region of particular interest due to the large number of injuries to which it is subject. Thus, the detailed study of its anatomical structure, size and elemental composition is justified for the improvement of diagnostic techniques, treatment and prevention of injuries. In this work it has been studied the macro elemental composition of 30 pairs of equine third metacarpal bone and its relation with age, sex, weight, breed, nutrition and activity of animals. The average concentrations of calcium and phosphorus of the samples were 205 ± 62 mg/g and 97 ± 32 mg/g, respectively. The ratio [Ca] / [P] was found to be 2.12 ± 0.13, indicating that the ratio of calcium and phosphorus in bone tissue is constant and approximately equal to the ratio 2:1. The statistical analysis showed normal values for the entire set of measurements. In the evaluation of the animals with intense physical activity, and animals with light physical activity, it was found that the amount of mineralized material for the first and second sets respectively ([Ca] = 222 ± 57 mg/g [Ca] = 179 ± 47 mg/g), showing the existence of statistical correlation between the deposit of mineral material and the function performed by the animals. For the other characteristics were not found statistical evidence of correlations. These findings will be input for further studies of possible correlations with diseases of nutritional origin or physiological outside the series of fractures and other disease common to the equine locomotor system.